Use of Visual Idioms in the Novel Written by Souvanthone Bouphanouvong - AMPHAITHIP, Khampha; SAN, Somephet (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purpose of this study was to investigate the visual idiom in the novel by Souvanthone Bouphanouvong. The qualitative research was deployed in this study and the researchers thoroughly examined the existing documents as well as a variety of research papers relating to visual idioms appeared in the novel of “Second Battalion” and Two sisters” for 7 volumes in order to analyze them based on the theory of Saythip Noukhounkhit. After that all analyses were capitulated, interpreted through the descriptive method. The study found that the visual effects that appear in all 15 of Souvanthone Bouphanouvong’s novels reflect the beauty of the language that the author chooses to use to introduce his story, social life through simple, diverse languages ​​that can communicate well. There is the application of locally-used words, expressions in the language, the use of emotional words, the use of metaphors that are imaginative, fun, funny, beautiful and elaborate. These can make the readers are emotional, impressed and able to visualize the story, events, phenomena, actions that the author wants to convey clearly.